2004
DOI: 10.14507/epaa.v12n45.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between State and District Content Standards:Issues of Alignment, Influence and Utility

Abstract: At the core of standards-based reform are content standards--statements about what students should know and be able to do. Although it is state standards that are the focus of much public attention and consume substantial resources, many local school districts have developed their own content standards in the major subject areas. However, we know very little about the role state standards have played in local standards efforts. In this article we report on a study of the relationship between state and local co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…In these cases, contradictions are viewed as negative features of the policy context that lead to negative outcomes for implementers and beneficiaries alike. Additionally, previous research has revealed that there can be contradictions between public policies that create problems in implementation contexts (Burton et al;Dutro & Valencia, 2004). Taken in conjunction with previous communicationbased research, these studies indicate that much remains to be explored regarding communication and contradictions in the policy knowledge process.…”
Section: Policy Knowledgesupporting
confidence: 58%
“…In these cases, contradictions are viewed as negative features of the policy context that lead to negative outcomes for implementers and beneficiaries alike. Additionally, previous research has revealed that there can be contradictions between public policies that create problems in implementation contexts (Burton et al;Dutro & Valencia, 2004). Taken in conjunction with previous communicationbased research, these studies indicate that much remains to be explored regarding communication and contradictions in the policy knowledge process.…”
Section: Policy Knowledgesupporting
confidence: 58%
“…Here we are reminded of the origin of standards-based reform and a focus on the ends or outcomes, giving school districts and schools flexibility on the means (National Research Council, 1999). We can imagine a return to common curriculum frameworks or content standards that are at a moderate level of specificity (Dutro & Valencia, 2004). These could guide, rather than prescribe, instruction and could encourage multiple instructional strategies and programs.…”
Section: Curriculum Mandatesmentioning
confidence: 99%
“…Keywords Survey Á Teacher attitudes Á State writing standards Á State writing assessments Intoduction Educational policy research suggests that both learning standards and large-scale assessments in the domain of writing influence teachers' writing instruction (Albertson, 2007;Hillocks, 2002;McCarthey, 2008;O'Neill, Murphy, Huot, & Williamson, 2006;Scherff & Piazza, 2005;Stecher, Barron, Chun, & Ross, 2000;Taylor, Shepard, Kinner, & Rosenthal, 2003), though assessments may exert a stronger effect on teacher behavior because accountability tests have ''teeth'' and because standards are more open to interpretation as the intended curriculum and are filtered through teachers' experiences, beliefs, and attitudes (e.g., Dutro & Valencia, 2004;Klein, Hamilton, McCaffrey, & Stecher, 2000). In the survey study reported here, we focus on teachers' perceptions of one of the recent widespread educational policy changes in the United States-the adoption and implementation of the Common Core State Standards and aligned accountability assessments.…”
mentioning
confidence: 99%